Studi Kelayakan Ekonomi Pembangunan PLTD Sistem Dual Fuel dengan Gasifikasi Sekam Padi Kapasitas 50 kVA - Syamsul Ma`arif; Rena Juwita Sari; Mochamad Syamsiro (Universitas Janabadra, 2016)
Electrification ratio in Special Distric of Yogyakarta in 2015 still under 100%, but 100% villages has been electrified. It shows that several houses which far from village which has not been electrified. The alternative solution is to build a small power plant by utilizing rice husks which are quite abundant in Yogyakarta. Diesel Power Plant (PLTD) by dual fuel system studied had a capacity of 50 kVA. Dual fuel system is combination of diesel fuel and synthetic gas from gasification of rice husks. This study is discussed about potential of rice husks, gasification equipment design, electrical distribution, and economic feasibility studies. The results showed that 0.2% of rice husks in Yogyakarta is enough to fulfill fuel requirements of PLTD by dual fuel system. Comparison of fuel requirements in PLTD by dual fuel system is 40% or about 4.72 liters/hour of diesel fuel and 60% synthetic gas from gasification of rice husk as much as 33.19 kgs/hour. Reactor is designed to fulfill gasification process for 2 hours every batch. The system produced 31.68 kWh distributed to 2 home industries, 48 households with each capacity is 450 VA, and street lighting. Investment to build PLTD by dual fuel system is Rp. 700,310,500.00 and operational & maintenance costs is Rp. 458,196,000.00 per year. The economic feasibility study to build PLTD by dual fuel system is claimed feasible if minimum price of electricity is Rp. 2,417.00 which gain NPV and IRR of Rp. 568,819.00 and 12.03%,respectively and payback period of 4 years.